2012
DOI: 10.1016/j.pec.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Interpreter perspectives of in-person, telephonic, and videoconferencing medical interpretation in clinical encounters

Abstract: Objective-To examine professional medical interpreters' perspectives of in-person and remote interpreting modalities.Methods-Survey of interpreters at three medical centers assessing satisfaction with aspects of communication using each modality, and adequacy of videoconferencing medical interpretation (VMI) and telephonic interpretation for 21 common clinical scenarios in the hospital and ambulatory care settings.Results-52 interpreters completed the survey (73% response). All modalities were equally satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 33 publications
(27 reference statements)
3
66
0
1
Order By: Relevance
“…In considering the quality of family interpretations in general medicine, Meeuwesen et al (2010) raised concerns with regard to miscommunication from changes in translation to side-talk activities. Professional medical interpreters have been found to be highly successful in remote contexts using telephone-based interpreting (Price et al, 2012); however, viewing interpreters as ‗smart technology' in face to face consultations was seen as open to possible interpersonal and ethical dilemmas (Hsieh and Kramer, 2012). Flores et al (2012) indicated the critical training period for success with omission, addition, substitution, editorialization and false fluency reduced significantly for non-trained interpreters after 100 hours of training.…”
Section: Professional Interpretingmentioning
confidence: 99%
“…In considering the quality of family interpretations in general medicine, Meeuwesen et al (2010) raised concerns with regard to miscommunication from changes in translation to side-talk activities. Professional medical interpreters have been found to be highly successful in remote contexts using telephone-based interpreting (Price et al, 2012); however, viewing interpreters as ‗smart technology' in face to face consultations was seen as open to possible interpersonal and ethical dilemmas (Hsieh and Kramer, 2012). Flores et al (2012) indicated the critical training period for success with omission, addition, substitution, editorialization and false fluency reduced significantly for non-trained interpreters after 100 hours of training.…”
Section: Professional Interpretingmentioning
confidence: 99%
“…[17][18][19] However, compared to on-site interpreting, telephone interpreting is often rated lower for interpersonal rapport due to a lack of nonverbal communication and problematic discursive style (e.g., repetition and slowed speech). 9,[20][21][22][23] Providers using videoconference interpreting report less understanding about patients' cultural beliefs than those who use on-site interpreting, 19 making videoconference interpreting a problematic choice when cultural competency is important (e.g., end-of-life care).…”
mentioning
confidence: 99%
“…Nevertheless, both are shared attitudes for providers across all specialties. Several qualitative studies have noted the conflicting desires for providers and interpreters, as they negotiate and manage different aspects of care, including therapeutic objectives, interpersonal relationships, education, and empathy, among others (Fatahi et al, 2008; Hsieh, 2006a; Price, Pérez-Stable, Nickleach, Lopez, & Karliner, 2012). If the providers and interpreters are not aware of the competing demands and expectations, they may experience a general sense of frustration or confusion without a clear strategy for resolving such a dilemma (Butow et al, 2011; Fatahi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several studies have systematically examined the differences between professional and family interpreters in their discursive strategies and in providers’ expectations (Leanza, Boivin, & Rosenberg, 2010; Rosenberg et al, 2007; Rosenberg, Seller, & Leanza, 2008). Other scholars have examined how different modes of interpreting (e.g., in-person, video, and telephonic interpreting) may influence patient satisfaction, provider evaluation, and interpreters’ communicative strategies (Locatis et al, 2010; Nápoles et al, 2010; Price et al, 2012). This line of research advances past literature by abandoning the untested presumption that trained interpreters are always better in all situations.…”
Section: Discussionmentioning
confidence: 99%